Corporate Social Responsibility and Financial Performance: Evidences from the Nigerian Industrial and Consumer Sector - Oladeji Ige Olubunmi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The issue of corporate social responsibility has attractive more attention recently as result of its contribution towards stakeholders. This study investigated Corporate Social Responsibility (CSR) on financial performance of some selected manufacturing companies in Nigeria. Ex-post facto research design was used for the study. The study population comprised of all customer goods and industrial sectors of manufacturing companies in Nigeria among which fifteen (15) of them were selected using purposive sampling technique for the period of 2010-2019. Secondary data were collected from the annual report the sampled companies. Two hypotheses were formulated and tested. Both descriptive and inferential statistics (correlation and multi - regression) were used for data analysis. The result of analysis revealed that CSR has significant relationship on financial performance measured with EPS and negative significant relationship on NPM of selected manufacturing companies in Nigeria